Bile acids specifically increase hepatitis C virus RNA-replication - Chhatwal, Patrick; Schult, Philipp; Lohmann, Volker (PLOS ONE, 2012)
Background Hepatitis C virus (HCV) patients with high serum levels of bile acids (BAs) respond poorly to IFN therapy. BAs have been shown to increase RNA-replication of genotype 1 but not genotype 2a replicons. Since BAs modulate lipid metabolism including lipoprotein secretion and as HCV depends on lipids and lipoproteins during RNA-replication, virus production and cell entry, BAs may affect multiple steps of the HCV life cycle. Therefore, we analyzed the influence of BAs on individual steps of virus replication. Methods We measured replication of subgenomic genotype (GT) 1b and 2a RNAs as well as full-length GT2a genomes in the presence of BAs using quantitative RT-PCR and luciferase assays. Cell entry was determined using HCV pseudoparticles (HCVpp). Virus assembly and release were quantified using a core-specific ELISA. Replicon chimeras were employed to characterize genotype-specific modulation of HCV by BAs. Lunet CD81/GFP-NLS-MAVS cells were used to determine infection of Con1 particles. Results BAs increased RNA-replication of GT1b replicons up to 10-fold but had no effect on subgenomic GT2a replicons both in Huh-7 and HuH6 cells. They did not increase viral RNA translation, virus assembly and release or cell entry. Lowering replication efficiency of GT2a replicons rendered them susceptible to stimulation by BAs. Moreover, replication of full length GT1b with or without replication enhancing mutations and GT2a genomes were also stimulated by BAs. Conclusions Bile acids specifically enhance RNA-replication. This is not limited to GT1, but also holds true for GT2a full length genomes and subgenomic replicons with low replication capacity. The increase of HCV replication by BAs may influence the efficacy of antiviral treatment in vivo and may improve replication of primary HCV genomes in cell culture.